Asymmetrische Hirndurchblutung im Alter? - Bekier, A. (Nuklearmedizin - NuclearMedicine, 1976)
Between 1971 and 1975 we performed 1580 dynamic perfusion studies in 1411 patients. The patients were admitted to the nuclear medicine department for brain scanning from the medical, neurological and neurosurgical departments as well as directly by private family physicians.For dynamic brain studies we used the scintillation camera (Searle Radiographics) and a bolus of 99mTc-pertechnetate intravenously injected. The polaroid frames were exposed at 4 second intervalsThe results of the dynamic brain study were divided into five categories: normal, moderately diminished perfusion of one hemisphere, severe perfusion defect of one hemisphere, focal or multifocal hypervascular areas (“hot areas”) and stenosis or occlusion of the carotid artery.In 1009 cases we found a normal perfusion of the tracer material without any side difference between the brain hemispheres.In 68 patients with motoric hemisyndrome of the right side and in 89 patients with hemisyndrome of the left side we were able to demonstrate a diminished perfusion of the contralateral hemisphere.In 65 patients with confirmed primary or metastatic brain tumors we observed a perfusion deficiency in 39 cases and focal “hot” areas in 26 cases.In 24 epileptic patients we found asymmetrical perfusion of the brain.In 109 patients without any neurological signs or symptoms we registered a “false positive” dynamic perfusion study with an asymmetrical initial transition of the injected tracer material.The left hemisphere showed a diminished perfusion in 86 cases, the right in 23 cases.The asymmetrical brain perfusion was not observed in patients under the age of twenty years.The incidence of “false positive” dynamic brain studies was found to be dependent on the age of the investigeted patients with a maximum of asymmetrical brain perfusion scans in the age group between 61 and 70 years.At present time we are not able to explain the reason of the “false positive” results. Because of this reason the investigation will be continued together with the neurologists and radiologists to find out a possible correlation between our study, the EEG-curves and results of the morphological brain investigations such as pneumoencephalography or ACT-scans.